Problems and prospects of implementing circular economy models in construction - Futnikov, V.; Chupryna , Yu. (Ways to Improve Construction Efficiency, 2022)
Implementation of Circular Economy (CE) models in the construction sector is becoming a key direction in transforming modern construction toward increased resource efficiency, reduced environmental impact, and sustainable development. Growing demands for environmental responsibility, energy efficiency, and cost optimization drive enterprises to adopt concepts of recycling, material reuse, and maximizing the lifecycle of construction resources. Circular models involve comprehensive integration of managerial, technological, and analytical solutions that enable the monitoring of material flows, reduction of waste generation, and enhancement of the economic returns of projects. A critical aspect is the combination of digital technologies, including BIM, ERP systems, and Big Data analytics platforms, with sustainable resource utilization practices. This integration allows for transparent models of planning and lifecycle control of construction materials, optimization of logistics flows, and effective coordination among all participants in construction processes. Special attention is given to the challenges of integrating CE into existing construction practices. The primary challenges include high initial investment costs, the absence of standardized methodologies for evaluating the effectiveness of circular solutions, the need to transform corporate culture and train personnel, and adaptation to regulatory requirements and safety standards. Nevertheless, the prospects of implementing CE include significant reductions in construction material intensity, increased competitiveness of companies, development of new business models, and enhancement of the sector’s innovation potential. By developing a systematic approach to implementing circular economy principles in construction, it is possible to achieve improved economic efficiency, sustainable environmental performance, and comprehensive management of construction resources. The proposed conceptual framework can serve as a basis for further research, development of methodological recommendations, and practical implementation of innovative management models in construction companies seeking to integrate circular economy principles into their projects.